Pengaruh latihan full court drill three man weave terhadap peningkatan daya tahan vo2 max dan keterampilan passing pada pemain putra klub basket dertien Mataram tahun 2022 - Zikri Kuriawan; Aminnullah; Lalu Hulfian (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2023)
in 2022. This research employed a quantitative method, with a population consisting of all 20 players of the Dertien Mataram basketball club, using a total sampling technique. To measure VO₂ max endurance and passing skills, the instruments used were the bleep test and a passing accuracy test.The results showed that VO₂ max endurance in the pretest had a maximum score of 41.5 and a minimum of 27.2, while in the posttest the maximum score increased to 42.0 and the minimum to 27.8. Meanwhile, passing skills in the pretest had a maximum score of 12 and a minimum of 7, and in the posttest the maximum score increased to 14 and the minimum to 10. Based on the t-test calculation, the result for VO₂ max endurance was 7.225, and for passing skills was 12.650.